La tecnología para potenciar el desarrollo de la inteligencia intrapersonal de los niños de preparatoria de la escuela de educación básica municipal héroes del cenepa de la ciudad de Loja periodo lectivo 2018 – 2019 - Bravo Guzman, Olga Tatiana (2020)
This research entitled: THE TECHNOLOGY TO POWER THE DEVELOPMENT OF THE INTRAPERSONAL INTELLIGENCE OF CHILDREN OF PREPARATORY OF THE SCHOOL OF BASIC EDUCATION MUNICIPAL HEROES OF THE CENEPA OF THE CITY OF LOJA LECTIVE PERIOD 2018 - 2019, has as a general. technology to develop intrapersonal intelligence in high school children. For its development the methods are analyzed: descriptive, scientific, analytical-synthetic, statistical, inductive-deductive; the techniques and instruments applied were: the BarOn Ice test to know the level of intrapersonal intelligence present in children, survey parents to determine the presence of technology in homes; to teachers to know the understanding of intrapersonal intelligence and technological presence; The sample investigated was 4 teachers, 29 children and parents. In the literature review two variables will be addressed: technology and intrapersonal intelligence; The results obtained in the pre-test show that most of the sample corresponding to 75.86% are at levels that need to be improved, therefore the need to propose activities that enhance intelligence is evidenced, and this is the case wait, have applied the proposal "mirror, mirror who am I?" which is based on the use of technological resources will reduce the percentage by 34.48%, reaching the conclusion that technological resources allow to enhance the development of the intrapersonal intelligence thanks to the use of audio, image, animation, video, effects, etc., therefore it is necessary to promote good practices of technology use to incorporate ICT as an educational tool in the teaching-learning process.